The Deixis Analysis Of Donald Trump’s Victory Speech - Purwandhi, Dwi; Simatupang, Ervina CM (Lembaga Penelitian Universitas Pasundan, 2025)
This study aims to describe the use of deixis in Donald Trump’s 2024 Victory Speech. Employing a descriptive qualitative method, the research focuses on analyzing the types and frequency of deixis found within the speech text. The primary data source is the official transcript of the speech. The research process involved collecting, selecting, and reducing relevant data, particularly sentences or words containing deixis. The data were then displayed and analyzed to identify the types of deixis used. The study concludes by interpreting the findings and determining the most dominant type of deixis in the speech delivered by Donald Trump. Based on the analysis, five types of deixis were identified: person deixis, spatial or place deixis, temporal or time deixis, discourse deixis, and social deixis. A total of 344 deictic expressions were found in the speech. Among these, person deixis was the most frequently used, with 279 occurrences, representing 81.10% of the total. This suggests that Donald Trump heavily relied on personal references, such as pronouns like “I,” “we,” “you,” and “they,” to engage his audience and emphasize personal and collective identity. The dominance of person deixis indicates a rhetorical strategy aimed at establishing a strong connection with listeners, reinforcing solidarity, and asserting leadership. The findings highlight the importance of deixis as a linguistic tool in political discourse, particularly in persuasive and emotionally charged speeches. This study contributes to the broader understanding of how linguistic features like deixis function in political communication to influence public perception and audience response.